"I Try… but Do I Succeed?": Representing the Diversity of Australian Culture in the National Library of Australia's Catalog. Issue 6 (3rd October 2022) - Boyd, Jodie
Abstract: In a survey of catalogers at the National Library of Australia, perceptions were sought on how effective they felt themselves and their tools to be in constructing a catalog able to enact the NLA's vision to "connect all Australians with national collections". The survey found that a significant proportion of catalogers were cognizant of long-standing concerns about standardizing tools and practices working to reinforce a binary and contributory understanding of "cultural diversity" that is at odds with both institutional policy goals and broader values relating to citizenship within a plural, multicultural construct of the Australian nationality.